Cytoreductive surgery with intraperitoneal chemotherapy in the management of peritoneal surface malignancy: a pharmacist's perspective. Issue 4 (5th April 2016) - Mistry, Priya; Mohamed, Faheez; Dayal, Sanjeev; Cecil, Tom D; Moran, Brendan J
Abstract : Objectives: To explore the use of intraperitoneal chemotherapy in conjunction with cytoreductive surgery for the treatment of peritoneal surface malignancy and highlight the challenges this provides for the hospital pharmacist. Methods: A literature search for relevant articles was performed using MEDLINE, PubMed and Cochrane databases. The following keywords and phrases were used: 'hyperthermic intraperitoneal chemotherapy', 'early postoperative intraperitoneal chemotherapy', 'carrier solutions' and 'cytoreductive surgery'. Local experience was also shared, referencing national guidelines and published literature. Results: The rationale behind intraperitoneal chemotherapy is to directly administer drugs into the peritoneal cavity and achieve exposure of higher concentrations of cytotoxic agents to tumour nodules within the abdomen and on peritoneal surfaces for a prolonged period of time, without significant systemic toxicity. This has been widely demonstrated in intraoperative and early postoperative settings. Hydrophilic chemotherapy drugs with high molecular weights and permeable to the peritoneum, but slow plasma clearance create high concentrations of the drug in the peritoneal cavity, with lower systemic circulation. Commonly used drugs include mitomycin C, oxaliplatin, cisplatin, doxorubicin and 5-fluorouracil . Newer drugs such as the taxanes and bevacizumab have also shown promise. Heat increases drug penetration into body tissues and destroys tumour cells directly by causing damage to cells that have inherently faulty heat regulation pathways and also increases the cytotoxic effect of selected chemotherapeutic agents. Optimal temperature for hyperthermic intraperitoneal drug administration is between 41 and 43°C in a carrier solution that is compatible with the drug chosen. For early postoperative intraperitoneal chemotherapy high molecular weight starch carrier solutions prolong intraperitoneal dwell time and exposure of drug to tumour cells. Drugs are administered intraoperatively with the abdomen open or closed for between 30 and 120 min depending on the drug chosen and local protocols. Drug doses are traditionally calculated using body surface area. Toxicity such as neutropenia is encountered far less than with systemic chemotherapy. Conclusions: This paper discusses the rationale for intraperitoneal drug administration following cytoreductive surgery and describes appropriate drug selection, methods of drug delivery and potential challenges in the use of the intraperitoneal route. It provides evidence and practical guidance for hospital pharmacists who may be involved in the surgical management of peritoneal malignancy particularly in dose calculation, preparation and administration of intraperitoneal chemotherapy.